Clinical repigmentation patterns in paediatric vitiligo. (6th August 2016) - Gan, E.Y.; Gahat, T.; Cario‐André, M.; Seneschal, J.; Ezzedine, K.; Taïeb, A.
Summary: Background: Repigmentation is an essential outcome measure in vitiligo. However, clinical studies describing vitiligo repigmentation patterns are lacking. Objectives: To assess and clearly define the repigmentation patterns in a series of patients with vitiligo, correlating these with clinicoepidemiological characteristics. Methods: Patients with vitiligo seen at least at twice (initial consultation and follow‐up visit) in the Department of Paediatric Dermatology, Hôpital Pellegrin des Enfants, Bordeaux University Hospital from 2006 to 2014 were included. Clinical photographs and case records were reviewed. Results: There were 109 patients (64 female, 45 male) mostly with Fitzpatrick skin type III ( n  =   67, 61%). The majority had nonsegmental ( n  =   71, 65%) or segmental vitiligo ( n  =   29, 27%). In total 172 representative vitiligo lesions were analysed. Overall, a combined pattern of repigmentation was most commonly seen ( n  =   106, 62%). The combined pattern occurred more frequently in patients with segmental vs. nonsegmental vitiligo ( P  =   0·009), whereas the diffuse pattern was more frequent in the latter ( P  =   0·007). Diffuse repigmentation was the predominant pattern on the eyelids ( P  <   0·001). We observed a new pattern in sites with few to absent hair follicles, which we propose to call 'medium spotted repigmentation'. This begins as circular macules of repigmentation, wider than 5 mm in diameter, which, from the outset, are larger than the initial macules of perifollicular repigmentation. This study is limited by its retrospective nature and small sample size for subgroup assessment. Conclusions: The combined pattern of repigmentation was most frequently observed. Medium spotted repigmentation is a new pattern, which will benefit from larger studies for a better understanding. Abstract : What's already known about this topic? Four repigmentation patterns have been described in vitiligo so far: perifollicular, marginal, diffuse and combined. The perifollicular repigmentation pattern tends to be more common in reported studies. What does this study add? A fifth repigmentation pattern, medium spotted repigmentation, occurs in areas with low hair follicle density, such as the glabrous areas, ankles and wrist flexors. The combined pattern of repigmentation was the most frequently observed pattern in our cohort of paediatric patients with vitiligo. Linked Comment: Bishnoi and Parsad. Br J Dermatol 2016;175 :460–461 . Plain language summary available online